Biomarker screening and validation for the differentiation of bloodstream infection from adult-onset Still's disease: A prospective cohort study. (October 2021) - Zhang, Wei; Yang, Tao; Zhang, Haocheng; Xu, Yuzhen; Yang, Qingluan; Liu, Qianqian; Gao, Yan; Wu, Jing; Shao, Lingyun; Zhang, Wenhong
Graphical abstract: Highlights: PCT, IL-6, IL-17A, CX3CL1, and CXCL10 levels were higher in patients with BSI. Ferritin and IL-18 levels were higher among patients with AOSD. A combination of plasma IL-18 and ferritin levels can be used to distinguish BSI from AOSD. Plasma IL-18 levels were positively correlated with ferritin. Plasma IL-18 decreased after treatment in both BSI and ASOD groups. Abstract: Objectives: Distinguishing between bloodstream infection (BSI) and adult-onset Still's disease (AOSD) is challenging in practice due to similarities in their clinical and laboratory characteristics. We aimed to identify biomarkers in a prospective cohort of patients with BSI and AOSD for differential diagnosis and prognosis prediction. Methods: Sixty-four individuals were enrolled in the training set (37 with BSI, 17 with AOSD, and 10 healthy controls). Furthermore, 86 individuals were enrolled in the validation cohort (67 with BSI and 19 with AOSD). Clinical and laboratory data were collected. Blood samples were stimulated using bacteria-specific antigens and levels of several cytokines were detected in the supernatant via Luminex or enzyme-linked immunosorbent assay. Results: Escherichia coli and Klebsiella pneumoniae were the pathogens most frequently responsible for BSI. In the training cohort, the incidence of rash, arthralgia, myalgia, sore throat, lymphadenopathy, leukocytosis, and hyperferritinemia was higher in patients with AOSD than in those with BSI. Procalcitonin was significantly higher in patients with BSI than that in those with AOSD. Interleukin (IL)-6, IL-17A, C-X3-C motif chemokine ligand (CX3CL)-1, and C-X-C motif chemokine ligand 10 (CXCL10) levels were higher in patients with BSI than in those with AOSD. IL-18 was higher among patients with AOSD than in those with BSI. A decision tree analysis showed that a combination of plasma IL-18 and ferritin levels can be used to distinguish BSI from AOSD (diagnostic accuracy: 97.67%, sensitivity: 96.15%, specificity: 100%). Plasma IL-18 levels were positively correlated with ferritin, and were decreased after treatment in both BSI and ASOD groups. Conclusions: Plasma IL-18 and ferritin levels can be used to differentiate BSI from AOSD. IL-18 may be a potential biomarker for prognosis prediction in BSI and AOSD.